Answer:
f(x)^-1 = x/4
Step-by-step explanation:
f(x)=4x
inverse
x = 4y
rewrite
4y = x
y = x/4
Answer:
f(x)^-1 = x/4
Answer:
<u><em>y=7 </em></u><u>number of hours at grocery store</u>
<u><em>x=18 </em></u><u>number of hours at baby- sitting</u>
Step-by-step explanation:
According to the information provided.
x is number of hours at baby- sitting
y is number of hours at grocery store
total number of hours worked
<em>1) </em><em>x+y =25</em>
total earn in a week
<em>2) </em><em>x*$6 + y* $9 = $171</em>
<em />
<em>from equation 1</em>
x+y=25
x= 25-y
<em>we place the above derived equation in equation 2 </em>
x*$6 + y* $9 = $171
(25-y)*$6 + y* $9 = $171
(25*6) -6y +9y =171
150+3y=171
3y=171-150
3y=21
<u><em>y=7 </em></u><u>number of hours at grocery store</u>
x= 25-y
x= 25-7
<u><em>x=18 </em></u><u>number of hours at baby- sitting</u>
So if 24 people chose popcorn and there is a total of 60 people surveyed, the fraction would be 24/60. You still need to simplify the fraction, so divide 24/60 by 4 to get 6/15. Hope this helps. -S
wait i will take screen shot please bran-list
What grade is this i think ive done this before i may be able to help